2017
DOI: 10.3892/or.2017.5739
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA C5orf66-AS1 is downregulated in pituitary null cell adenomas and is associated with their invasiveness

Abstract: Pituitary null cell adenoma is a challenging clinical condition, and its pathogenesis remains to be elucidated. We performed this study to determine the roles of C5orf66-AS1, NORAD, and TINCR in the pathogenesis and invasion of pituitary null cell adenomas. Expression of the three long non-coding RNAs in pituitary null cell adenoma tissues of 11 patients and normal pituitary tissues from four donors was examined by performing quantitative reverse transcription-polymerase chain reaction. We found that C5orf66-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…C5orf66-AS1 is a lncRNA that is expressed highest in the pituitary, but it is also associated with cancer in other cell types. It was found to be lower expressed in eleven NF-PitNET samples than four normal pituitary tissues and was moreover inversely correlated with invasive tumor behavior, indicating a tumor suppressive role [68].…”
Section: Long Non-coding Rnasmentioning
confidence: 96%
“…C5orf66-AS1 is a lncRNA that is expressed highest in the pituitary, but it is also associated with cancer in other cell types. It was found to be lower expressed in eleven NF-PitNET samples than four normal pituitary tissues and was moreover inversely correlated with invasive tumor behavior, indicating a tumor suppressive role [68].…”
Section: Long Non-coding Rnasmentioning
confidence: 96%
“…In addition, the expression of lncRNA MEG3 and HOTAIR was also related to non-functioning pituitary adenomas (NFPAs) invasion [23,24]. LncRNA C5orf66-AS1 suppressed the development and invasion of pituitary null cell adenomas [25]. In pituitary prolactinoma, one of the most prevalent types in pituitary adenoma, lncRNA CLRN1-AS1 regulated cell growth and autophagy by acting as a ceRNA to suppress the Wnt/β-catenin signaling pathway [26].…”
Section: Of 17mentioning
confidence: 99%
“…As a competitive endogenous RNA (ceRNA), c5orf66-as1 regulates RING1 and affects the proliferation, apoptosis and cell cycle of cervical cancer cells by absorbing miR-637. Regarding its distribution and effect in PAs, Yu et al [85] demonstrated that the expression of c5orf66-as1 is downregulated in null cell pituitary adenoma compared with normal pituitary tissues, and the expression in invasive adenoma is lower than that in non-invasive adenoma, suggesting c5orf66-as1 is negative correlation with tumor invasiveness. In vitro assessments showed that the overexpression of c5orf66-as1 in PAs significantly inhibits cell activity and invasiveness, indicating that this lncRNA may act as an anti-tumor agent in null cell pituitary adenomas.…”
Section: C5orf66-as1mentioning
confidence: 99%